Analisis Pengembangan Sumber Daya Manusia Dalam Meningkatkan Kinerja Pegawai di Dinas Perpustakaan Dan Arsip Kabupaten Nias Barat - Dion Nisius Yasaro Gulo; Fatolosa Hulu; Palindungan Lahagu; Peringatan Harefa (Jurnal Ilmiah METANSI ”Manajemen dan Akuntansi”, 2024)
Study This analyze development source Power man And performance employee at the Library and Archives Service Regency West Nias . There is observed problems by researcher that is The training provided to employees is still inadequate, as seen from the fact that training activities are rarely carried out and often not held, so this hampers efforts to develop adequate human resources. Besides that, employees are still not punctual to work. Study This aim , to analyze resource development Power man in increase performance employee at the Library and Archives Service Regency West Nias . In do study This use method study qualitative with use technique data analysis ie data reduction , data presentation and withdrawal conclusion . Results study This show that Human resource development has been carried out well, however one of the obstacles faced in carrying out training activities is related to budget limitations. Then para employee Already produce good performance with exists punctuality in work, to achieve work targets.